New abelisaurid remains from the Anacleto Formation (Upper Cretaceous), Patagonia, Argentina. (May 2015) - Gianechini, Federico A.; Apesteguía, Sebastián; Landini, Walter; Finotti, Franco; Juárez Valieri, Rubén; Zandonai, Fabiana
Abstract: New theropod remains with abelisaurid affinities from the Upper Cretaceous (Anacleto Formation, lower Campanian), NW Patagonia, Argentina, are here described. The specimen (MPCN-PV 69) consists of a partial premaxilla, fragmentary vertebrae, proximal portion of both humeri, distal portion of the pubis, and an incomplete pedal ungual. Characters linking with Abelisauridae are a premaxilla with a subquadrangular body, externally ornamented, and paradental plates with a striated surface; and humerus with bulbous proximal head, conical internal tuberosity, and reduced greater tubercle. The humerus is similar to those of Carnotaurus and Aucasaurus, due to the presence of a bulbous head and a discontinuity between the head and the internal tuberosity, but also differs from both taxa in the more distal location of the greater tubercle with respect to the internal tuberosity. Aucasaurus also comes from Anacleto Formation, but differences in the humeri suggest that MPCN-PV 69 is a different taxon. The phylogenetic analysis performed supports the affiliation to Abelisauridae, but fails to determinate a more precise relationship with others abelisaurids. However, a majority rule consensus of the analysis shows a position within Brachyrostra. Despite being fragmentary, MPCN-PV 69 probably represents a new abelisaurid from the Anacleto Formation, thus increasing the knowledge and diversity of Late Cretaceous South American abelisaurids. Highlights: We describe new theropod remains from Anacleto Fm. (Campanian), Patagonia. The specimen (MPCN-PV 69) is phylogenetically related with abelisaurids. MPCN-PV 69 probably represents a new abelisaurid taxon. Abelisaurus could be morphologically and phylogenetically linked to Brachyrostra.